Search for genetic markers determining the efficiency of therapy with bisphosphonates in Russian women with postmenopausal osteoporosis: A pilot study - M. Yu. Krylov; O. A. Nikitinskaya; E. Yu. Samarkina; N. V. Demin; N. V. Toroptsova (Научно-практическая ревматология, 2016)
Many clinical observations show that patient’s genetic background is of great importance in determining the efficiency of treatment.Subjects and methods. The instigation included 50 postmenopausal women with osteoporosis (OP), who were followed up at the Laboratory of osteoporosis, V.A. Nasonova Research Institute of Rheumatology. Body mineral density (BMD) in the lumbar spine (LI-IV), femoral neck (FN), and total hip was measured using dual-energy X-ray absorptiometry before and 12 months after treatment with bisphosphonates (BP). To estimate BMD changes, the investigators used ΔBMD in percent (Δ, %).Results and discussion. The whole group showed a positive effect of BP therapy during a year, which was most pronounced in the lumbar spine (mean ΔBMD, about 4%), and a small increment in the proximal hip BMD (mean ΔBMD, about 2%). An analysis indicated a statistically significant correlation of MCP1 -2518A>G polymorphism with changes in LI-IV BMD after 12-month BP therapy. Thus, the female patients who were A allele carriers had a twice lower increase in LI-IV BMD due to BP therapy than those without this allele. The genetic variants of the CCR5 gene, which were related to Δ32 deletion, and IL1β -511C/T polymorphism were also associated with changes in FN BMD following 12-month BP therapy. The BMD increase due to BP therapy in the carriers of the CCR5 Δ32 mutation (wt/Δ32 genotype) was 3.5-fold than that in the carriers of the wild type gene (wt/wt genotype). Examination of IL1 -511C/T polymorphism demonstrated that the FN BMD increment in the carriers of the CC genotype was significantly higher than in those of the CT genotype (4.2±4.8 and 1.0±3.7%, respectively; р = 0.023). Our investigation revealed no significant relationship between VDR, LEPR, IL10, MHTFR, PPARG, SPP1, and CCR5(G/A) gene polymorphisms and 12-month BP therapy-induced BMD changes in the three study skeletal regions. The findings may suggest that genetic testing may be used to predict a response to BP.